Increased Serum Ferritin Levels in Type 2 Diabetes Mellitus Patients: A Hospital Based Cross-Sectional Study - Chaudhari, Rajendra Kumar; Niraula, Apeksha; Gelal, Basanta; Baranwal, Jouslin Kishore; Sarraf, Deependra Prasad; Maskey, Robin; Lamsal, Madhab Lamsal (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Type 2 diabetes mellitus is a metabolic disorder of multiple etiology characterized by chronic hyperglycemia with a derangement in carbohydrate, fat and protein metabolism resulting from defects in insulin secretion and action. Ferritin is a ubiquitous intracellular protein complex that reflects the iron stores of the body. Studies have shown that the increased body iron stores are associated with the development of glucose intolerance often leading to metabolic syndrome and type 2 diabetes (T2DM). The objective of the study was to find out association of serum ferritin level with T2DM and assess the correlation between serum ferritin and HbA1c. MATERIAL AND METHODS: A hospital based comparative cross-sectional study was conducted in 43 diabetic patients and 42 age and sex matched healthy controls. Fasting blood glucose (FBG), postprandial blood glucose (PBG), Glycated hemoglobin (HbA1c) and serum ferritin were estimated in cobas c311 autoanalyser using standard protocol. RESULTS: Mean age of healthy control and T2DM were found 54.83 ± 6.48 and 55.95±10.92 years respectively. Mean FBG (mg/dL) (170.41 ± 71.7 v/s 98.38 ± 9.7), PBG (mg/dL) (266.16 ± 110.09 v/s 123.20 ± 17.0), HbA1c (%) (8.17 ± 1.83 v/s 4.9 ± 0.29 and median ferritin (μg/L) 207.90 (138, 306.0) v/s 127.95 (85.75, 210.25) were significantly higher in T2DM compared to the healthy controls. Spearman’s correlation depicted that ferritin level was positively correlated with HbA1c level but the correlation was statistically insignificant. CONCLUSION: Serum ferritin level was found significantly higher in T2DM compared to healthy age and sex matched controls in our study.